CORPORA AND THE STUDY OF LANGUAGE EVOLUTION: A HISTORICAL LINGUISTICS PERSPECTIVE - Цанько, Іван (SWorldJournal, 2025)
This article explores the integration of diachronic corpora into historical linguistic research, focusing on their role in analyzing language change over time. The study outlines key diachronic corpora, such as the Helsinki Corpus of English Texts and th